Horten's incredible illusions : magic, mystery & another very strange adventure - Evans, Lissa (Sterling Children's Books, 2012)
Ten-year-old Stuart, having become the junior curator of the museum exhibition showcasing his great-uncle Tony's long-lost magic, enters the magical world of the workshop once more to find Tony's will and is faced with a series of puzzles that become harder and harder to solve.